Handbook of research on advances in data analytics and complex communication networks - Venkata Krishna, P. (Advances in wireless technologies and telecommunication (AWTT) book series., 2022)
"This edited book discusses data analytics and complex communication networks and recommends new methodologies, system architectures, and other solutions to prevail over the current limitations faced by the field"--